REINVENTING GOVERNMENT MANAGEMENT PADA KANTOR CAMAT LANGGAM KABUPATEN PELALAWAN - dailiati, surya; sudaryanto, sudaryanto (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
Langgam sub-district as one of the 12 sub-districts in Pelalawan District since the last 5 years continue to experience significant growth. Therefore, this research is conducted in Langgam District, especially this area is the hometown of the current Regent that is HM Harris. Various development programs have been implemented Pelalawan District Government to be able to turn this isolated village into a more advanced with the availability of roads and bridges. However, based on pre-survey conducted there are still some problems, namely: the lack of government facilities and infrastructure built by the government, the lack of private sector activities in Kecamatan Langgam and the lack of local products. To overcome this problem is done by qualitative descriptive approach. The theory used, according to David Osborn and Ted Gebler in Sinambela (2014), needs to apply ten principles of reinventing government management. District Government Langgam Pelalawan District has implemented Reinventing Government Management (Change Management Government) in carrying out daily tasks. It's just not in accordance with the wishes of the community. Positive things that seem to have been done diantaranta in terms of fulfillment of apparatus resources so as to be able to fill the ideal organizational structure